A Stress Response Monitoring Lipoprotein Trafficking to the Outer Membrane - Kerrie L. May (American Society for Microbiology, 2019)
ABSTRACT Gram-negative bacteria produce lipid-anchored lipoproteins that are trafficked to their outer membrane (OM). These lipoproteins are essential components in each of the molecular machines that build the OM, including the Bam machine that assembles β-barrel proteins and the Lpt pathway that transports lipopolysaccharide. Stress responses are known to monitor Bam and Lpt function, yet no stress system has been found that oversees the fundamental process of lipoprotein trafficking. We used genetic and chemical biology approaches to induce several different lipoprotein trafficking stresses in Escherichia coli. Our results identified the Cpx two-component system as a stress response for monitoring trafficking. Cpx is activated by trafficking defects and is required to protect the cell against the consequence of the resulting stress. The OM-targeted lipoprotein NlpE acts as a sensor that allows Cpx to gauge trafficking efficiency. We reveal that NlpE signals to Cpx while it is transiting the inner membrane (IM) en route to the OM and that only a small highly conserved N-terminal domain is required for signaling. We propose that defective trafficking causes NlpE to accumulate in the IM, activating Cpx to mount a transcriptional response that protects cells. Furthermore, we reconcile this new role of NlpE in signaling trafficking defects with its previously proposed role in sensing copper (Cu) stress by demonstrating that Cu impairs acylation of lipoproteins and, consequently, their trafficking to the OM. IMPORTANCE The outer membrane built by Gram-negative bacteria such as Escherichia coli forms a barrier that prevents antibiotics from entering the cell, limiting clinical options at a time of prevalent antibiotic resistance. Stress responses ensure that barrier integrity is continuously maintained. We have identified the Cpx signal transduction system as a stress response that monitors the trafficking of lipid-anchored lipoproteins to the outer membrane. These lipoproteins are needed by every machine that builds the outer membrane. Cpx monitors just one lipoprotein, NlpE, to detect the efficiency of lipoprotein trafficking in the cell. NlpE and Cpx were previously shown to play a role in resistance to copper. We show that copper blocks lipoprotein trafficking, reconciling old and new observations. Copper is an important element in innate immunity against pathogens, and our findings suggest that NlpE and Cpx help E. coli survive the assault of copper on a key outer membrane assembly pathway.